2022
DOI: 10.1111/ijfs.16081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidification and sterilisation on the quality of channel catfish (Ietalurus punctatus) fillets

Abstract: This study aims to investigate the effects of acidification and sterilisation on the quality of channel catfish, based on the texture, colour, physical and chemical properties, protein composition and water migration of channel catfish fillets. The results showed that the hardness, chewiness and colour of acidified and sterilised (AS) groups were significantly better than unacidified and sterilised (NAS) groups. The content of TCA soluble peptide in NAS was significantly higher than AS groups, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Yu et al . (2022) found that the hardness, springiness, and chewiness of the acidified fillets were superior to non‐acidified fillets, consistent with the results of this paper. After sterilisation at high temperature, the muscle fibre structure of the control group was destroyed, and the crayfish meat was browned, loosen, and unshaped (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Yu et al . (2022) found that the hardness, springiness, and chewiness of the acidified fillets were superior to non‐acidified fillets, consistent with the results of this paper. After sterilisation at high temperature, the muscle fibre structure of the control group was destroyed, and the crayfish meat was browned, loosen, and unshaped (Fig.…”
Section: Resultssupporting
confidence: 90%
“…High-temperature sterilisation prolongs the shelf life of the product, but it severely damages the protein structure and negatively affects the textural properties (Sun et al, 2021). Yu et al (2022) found that the hardness, springiness, and chewiness of the acidified fillets were superior to non-acidified fillets, consistent with the results of this paper. After sterilisation at high temperature, the muscle fibre structure of the control group was destroyed, and the crayfish meat was browned, loosen, and unshaped (Fig.…”
Section: Tpasupporting
confidence: 89%
See 2 more Smart Citations
“…For HAD, this may be due to WSP denaturation caused by high temperature, which leads to a decrease in WSP solubility. However, CHACD combines the characteristics of both drying methods, leading to a decrease in solubility [ 40 ]. When compared to the undried fresh samples, the SSP of CAD significantly increased from 6.93 to 8.15 mgN/g.…”
Section: Resultsmentioning
confidence: 99%